The last turtlemen of the Caribbean : waterscapes of labor, conservation, and boundary making - Crawford, Sharika D. (Flows, migrations, and exchanges., 2020)
"Crawford begins in the sixteenth century, laying out the stakes for the British and Spanish empires that first viewed the Caribbean as "an Atlantic commons"--An open space where all could compete to control diverse Caribbean peoples, lands, and waters and exploit the region's raw materials. Turning to the nineteenth and twentieth centuries, Crawford traces and connects the expansion and decline of turtle hunting to matters of race, labor, political and economic change, and the natural environment. Like the turtles they had chased, the boundary-flouting laborers exposed the limits of states' sovereignty for a time, but ultimately they lost their livelihoods, having played a significant role in legislation delimiting maritime boundaries. Still, today, former turtlemen have found their deep knowledge valued in efforts to protect sea turtles and recover the region's ecological sustainability"--